The Great Moderation: Inventories, shocks or monetary policy? - Marcel Förster (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper presents a New Keynesian DSGE model with inventory holding firms. The model distinguishes between goods and materials, for both production as well as for inventories. The more detailed treatment of inventory holdings offers new insights into the determinants of business cycles before and during the Great Moderation. Via Bayesian estimation we determine the distributions of the parameters for U.S. data for two subsamples. Our results show that impulse responses change significantly in terms of magnitude and persistence over time. Shocks in the labor market have gained importance since the Great Moderation and they explain the volatility of many variables. We reject the hypothesis of better inventory management and improved monetary policy as explanations for the Great Moderation. Instead, labor supply developments and changes in cost associated with capital play a key role for the reduced fluctuations.
Keywords: C13; E20; E30; 330; Inventories; Great Moderation; Bayesian Estimation; DSGE model; Business Cycles